Exploring an immune function for murine SARM - Gürtler, Claudia (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2012)
Innate immune cells, such as tissue-residing macrophages and dendritic cells (DCs) play a key role in initiating an immune response following the detection of invading pathogens via germline-encoded pattern-recognition receptors (PRRs) present on the cell surface or in intracellular compartments and the cytosol. PRRs selectively recognise conserved molecular features of the microbe and subsequently initiate distinct signalling cascades leading to transcription factor activation and the induction of proinflammatory cytokines (e.g. TNF-a), chemokines (e.g. CCL5/RANTES) and type I interferons (i.e. IFNa and IFN-β). One major family of PRRs are the membrane-bound Toll-like receptors (TLRs), which signal via the Toll/IL-1 receptor (TIR) domain-containing adaptor proteins IVIyD88, MAL, TRIP and TRAM. The immunological function of the fifth most evolutionarily conserved TIR adaptor sterile alpha and HEAT/Armadillo motif protein (SARM) is still enigmatic.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin.